Effect Of Hydrogen Peroxide Concentration on The Deacetylation Degree Of Chitosan Extracted From Maggot Waste - Titik Budiati; Silvia Oktavia Nur Yudiastuti; Agung Wahyono (Food Science and Technology Journal (Foodscitech), 2023)
The objective of this study was to determine the effect of hydrogen peroxide concentration on the deacetylation degree of chitosan extracted from maggot waste. Different hydrogen peroxide concentration (0%, 13%, 15%, and 20%) was studied. The degree of deacetylation of chitosan by using FTIR was found 75.3%, 77.6%, 78%, and 78.6% for a concentration of H2O2 of 0%, 13%, 15%, and 20%, respectively. The quality of chitosan extracted from the pupae shell of maggot waste meets the requirements of SNI 7949-2013. The concentration of H2O2 might increase the deacetylation degree of chitosan extracted from maggot waste.